Effect of dactylaria higginsii on purple nutsedge (Cyperus rotundus) interference with pepper (Capsicum annuum L) - Kadir, Jugah; Raghavan, Charudattan; Stall, William M.; Bewick, Tom A. (Universiti Putra Malaysia Press, 2000)
Greenhouse studies were conducted to evaluate the effect of the fungal pathogen, Dactylaria higginsii, on purple nutsedge interference with 'Capistrano' pepper (Capsicum annuum). Purple nutsedge plants established from tubers were planted at initial densities of 40, 80,160, and 320 plants m-2with pepper in 35-cm diam pots with a commercial potting medium, under nonlimiting fertilization and irrigation conditions. Three to four-leafstage purple nutsedge and four-leafstage pepper plants were inoculated by spraying D. higginsii in 0.5% Metamucil, a carrier; the treatments were carrier only, 104 conidia ml1 carrier, or 106 conidia conidia ml1 carrier. Purple nutsedge at all tuber densities significantly reduced pepper yield in the absence of D. higginsii. Percentage yield loss of pepper was greater in treatment with 104 conidia ml1• However, percentage yield loss of pepper was negligible in treatments with D. higginsii at 106 conidia ml1 when compared to the non-weedy control. The disease progress rate was significantly faster in treatments with 1(1 conidia ml1 (rc = 0.113 - 0.123) compared to 104 conidia mlJ (rc = 0.049 - 0.050). At 106 conidia ml1 , D. higginsii reduced nutsedge interference, provided greater nutsedge control, and increase pepper yield compared to weedy checks.